Differences in Anxiety in Second and Third Year Medical Undergraduate Students Faculty of Medicine, Nursing and Health Science, Universitas Gadjah Mada - Andrian Fajar Kusumadewi; Muhammad Alif Seswandhana; Afkar Aulia (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Anxiety is a condition in which a person experiences concern about an unpleasant event that will occur in the future. Medical students tend to experience anxiety during their studies. This study was attributable to the differences in anxiety in second and third-year medical students at the Faculty of Medicine Nursing and Health Science, Universitas Gadjah Mada. Methods: This research is an observational study with a cross-sectional design. The research will be conducted online using a self-reported questionnaire. Respondents' level of anxiety was measured by the general anxiety disorder-7 (GAD-7) questionnaire. Analysis of the data used is using the Mann-Whitney test method. Results: Of the total 109 respondents, the majority had a mild level of anxiety, with a total of 45 people. The majority of respondents are third-year students (59%), female (76%), and over 20 years old (69%). After analyzing using the Mann-Whitney Test between the GAD-7 score and the year of study, the p-value was 0.622. Conclusion: There is no difference in the level of anxiety in the second and third-year undergraduate medical students at the Faculty of Medicine, Nursing and Health Science, Universitas Gadjah Mada.